Arabidopsis AtMORC4 and AtMORC7 Form Nuclear Bodies and Repress a Large Number of Protein-Coding Genes - Harris, C. Jake (PLoS Genet, 2016)
The MORC family of GHKL ATPases are an enigmatic class of proteins with diverse chromatin related functions. In Arabidopsis, AtMORC1, AtMORC2, and AtMORC6 act together in heterodimeric complexes to mediate transcriptional silencing of methylated DNA elements. Here, we studied Arabidopsis AtMORC4 and AtMORC7. We found that, in contrast to AtMORC1,2,6, they act to suppress a wide set of non-methylated protein-coding genes that are enriched for those involved in pathogen response. Furthermore, atmorc4 atmorc7 double mutants show a pathogen response phenotype. We found that AtMORC4 and AtMORC7 form homomeric complexes in vivo and are concentrated in discrete nuclear bodies adjacent to chromocenters. Analysis of an atmorc1,2,4,5,6,7 hextuple mutant demonstrates that transcriptional de-repression is largely uncoupled from changes in DNA methylation in plants devoid of MORC function. However, we also uncover a requirement for MORC in both DNA methylation and silencing at a small but distinct subset of RNA-directed DNA methylation target loci. These regions are characterized by poised transcriptional potential and a low density of sites for symmetric cytosine methylation. These results provide insight into the biological function of MORC proteins in higher eukaryotes.